Analysis of Entrepreneurial Intentions in the Agricultural Sector (Agri-Preneur) of Agribusiness Students at Universities in Medan City - Muhammad Bobby Ramadhana; Retna Astuti Kuswardani; Emmy Harso Kardhinata; Muhammad Reza Aulia (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to identify students' entrepreneurial intentions at universities in Medan City. This research was conducted due to the issue of unemployment caused by the skill competencies of agribusiness graduates, the generally low interest among students in creating job opportunities, and the declining enthusiasm for entrepreneurship in the agricultural sector. This study employed a survey method with a research population consisting of 920 agribusiness students from the Faculty of Agriculture in Medan City, spread across three universities: UMA, UMSU, and USU. The sample for this study consisted of 90 students from the three universities. The results show that students' entrepreneurial intentions, particularly at universities in Medan City, demonstrate a high level of interest; however, there is a need for accelerated learning and hands-on practice in entrepreneurship. Entrepreneurial intention in Indonesia, especially at universities in Medan City, falls into the high category. The higher the personal values and personalities aligned with entrepreneurship among students, the higher their level of entrepreneurial intention. This indicates that the students' entrepreneurial intentions reflect a positive response toward entrepreneurship.